Activation of mGluR5 and Inhibition of NADPH Oxidase Improves Functional Recovery after Traumatic Brain Injury - Loane, David J. (Mary Ann Liebert, Inc., 2013)
Traumatic brain injury (TBI) induces microglial activation, which can contribute to secondary tissue loss. Activation of mGluR5 reduces microglial activation and inhibits microglial-mediated neurodegeneration in vitro, and is neuroprotective in experimental models of CNS injury. In vitro studies also suggest that the beneficial effects of mGluR5 activation involve nicotinamide adenine dinucleotide phosphate (NADPH) oxidase inhibition in activated microglia. We hypothesized that activation of mGluR5 by the selective agonist CHPG after TBI in mice is neuroprotective and that its therapeutic actions are mediated by NADPH oxidase inhibition. Vehicle, CHPG, or CHPG plus the mGluR5 antagonist (MPEP), were administered centrally, 30 minutes post-TBI, and functional recovery and lesion volume was assessed. CHPG significantly attenuated post-traumatic sensorimotor and cognitive deficits, and reduced lesion volumes; these effects were blocked by MPEP, thereby indicating neuroprotection involved selective activation of mGluR5. CHPG treatment also reduced NFκB activity and nitrite production in lipopolysaccharide-stimulated microglia and the protective effects of CHPG treatment were abrogated in NADPH oxidase deficient microglial cultures (gp91(phox-/-)). To address whether the neuroprotective effects of CHPG are mediated via the inhibition of NADPH oxidase, we administered the NADPH oxidase inhibitor apocynin with or without CHPG treatment after TBI. Both apocynin or CHPG treatment alone improved sensorimotor deficits and reduced lesion volumes when compared with vehicle-treated mice; however, the combined CHPG + apocynin treatment was not superior to CHPG alone. These data suggest that the neuroprotective effects of activating mGluR5 receptors after TBI are mediated, in part, via the inhibition of NADPH oxidase.